Altitude training and haemoglobin mass from the optimised carbon monoxide rebreathing method determined by a meta-analysis - Gore, Christopher John; Sharpe, Ken; Garvican-Lewis, Laura A.; Saunders, Philo U.; Humberstone, Clare E.; Robertson, Eileen Y.; Wachsmuth, Nadine B.; Clark, Sally A.; McLean, Blake D.; Friedmann-Bette, Birgit; Neya, Mitsuo; Pottgiesser, Torben; et al. (British journal of sports medicine, 2013)
Objective To characterise the time course of changes in haemoglobin mass (Hbmass) in response to altitude exposure. - Methods This meta-analysis uses raw data from 17 studies that used carbon monoxide rebreathing to determine Hbmass prealtitude, during altitude and postaltitude. Seven studies were classic altitude training, eight were live high train low (LHTL) and two mixed classic and LHTL. Separate linear-mixed models were fitted to the data from the 17 studies and the resultant estimates of the effects of altitude used in a random effects meta-analysis to obtain an overall estimate of the effect of altitude, with separate analyses during altitude and postaltitude. In addition, within-subject differences from the prealtitude phase for altitude participant and all the data on control participants were used to estimate the analytical SD. The ‘true’ between-subject response to altitude was estimated from the within-subject differences on altitude participants, between the prealtitude and during-altitude phases, together with the estimated analytical SD. - Results During-altitude Hbmass was estimated to increase by ∼1.1%/100 h for LHTL and classic altitude. Postaltitude Hbmass was estimated to be 3.3% higher than prealtitude values for up to 20 days. The within-subject SD was constant at ∼2% for up to 7 days between observations, indicative of analytical error. A 95% prediction interval for the ‘true’ response of an athlete exposed to 300 h of altitude was estimated to be 1.1-6%. - Conclusions Camps as short as 2 weeks of classic and LHTL altitude will quite likely increase Hbmass and most athletes can expect benefit.
Gesehen am 18.02.2020